Searching Smart on the World Wide Web: Tools and Techniques for Getting Quality Results - Gregory K. Raschke (Issues in Science and Technology Librarianship)
This article reviews the book Searching Smart on the World Wide Web: Tools and Techniques for Getting Quality Results. Internet Workshop Series Number 8. Berkeley: Library Solutions Press, 1998, by Cheryl Gould.